INVESTIGATING DISPARITIES IN METABOLITE CONCENTRATIONS USING GAS CHROMATOGRAPHY MASS SPECTROSCOPY AMONG PATIENTS WITH GESTATIONAL DIABETES MELLITUS AND IN HEALTHY CONTROL PARTICIPANTS - SAPNA BHARDWAJ; CHIRAG PASRICHA; PREETPAL SINGH; PRATIMA KUMARI; RUPINDER KAUR; RAVINDER SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Metabolomics has been a promising strategy in recent years for understanding the intricate metabolic changes linked to diseases like gestational diabetes mellitus (GDM). Gas chromatography-mass spectrometry (GC-MS) has been used as analytical method in this study to explore the function of metabolomics in comprehending the underlying biochemical alterations in GDM. Methods: One hundred subjects were enrolled and divided into two groups, Group A with healthy control participants (HCPs) and Group B with GDM patients. Both groups’ plasma samples were taken, and concentrations of amino acid metabolites were evaluated using GC-MS analysis. Results: Leucine and Tyrosine levels were low in HCP, that is, (1.79±0.15 μM and 0.25±0.06 μM), whereas levels were high in GDM patients, that is, (23.58±1.73 μM and 0.466±0.015 μM), respectively. Similarly, tryptophan and histidine levels were low in HCP, that is, (0.41±0.10 μM and 0.271±0.072 μM), and levels were high in GDM patients, that is, (0.871±0.105 μM and 1.916±0.340 μM), respectively. Methionine and Phenylalanine levels were high in HCP (1.063±0.161 and 0.642±0.035), and levels were low in GDM patients (0.765±0.103 and 0.459±0.056), respectively. Conclusion: The findings of the current study suggested that GDM is associated with an increase in tyrosine, tryptophan, leucine, and histidine levels and a decrease in methionine and phenylalanine levels. Therefore, these amino acids could serve as a diagnostic biomarker and supplementation tool (methionine and phenylalanine) as a management strategy in GDM.